Big Ideas, Little Pictures : Explaining the World One Sketch at a Time - Hey, Jono, ....- (New York : Media Lab Books, 2024)
Have you ever wondered what makes autumn leaves change color, why more choice makes you less happy or how to win at Monopoly? Or maybe you'd like to learn how to find your way using the stars or why we need worry less about what others think of us than you might expect. In Big Ideas Little Pictures, Jono Hey does the hard work for you by distilling fascinating and surprising topics into delightful and memorable sketches. Inside, you'll find insight and entertainment covering everything from the Swiss cheese model to what makes a perfect night's sleep. Big Ideas, Little Pictures is also a light-hearted, witty gift - the perfect display piece for anyone who wants something that can be picked up and flipped through, knowing they'll find something to pique their interest. Perfect for children as well as adults, Big Ideas, Little Pictures opens up a world of fascinating facts at a glance.
Keywords: Facts; Sketches